A Holocene record of millennial-scale climate changes in the mud area on the inner shelf of the East China Sea. (14th October 2015) - Li, Xiaoyan; Jian, Zhimin; Shi, Xuefa; Liu, Shengfa; Chen, Zhengbo; Wu, Yonghua; Shi, Fengdeng
Abstract: Core MZ01 from the mud area on the inner shelf of the East China Sea (ECS) was studied to detect millennial climate changes during the Holocene based on a modified version of accelerator mass spectrometry (AMS) 14 C dating age model, sediment grain size, oxygen isotopes and the Mg/Ca ratio of benthic foraminifera shells. On the basis of multiproxies of this core, eight abrupt cooling events were identified that occurred at 8.2, 7.2, 6.2, 5.1, 4.2, 3.2, 2.3 and 1.2 ka BP, within the uncertainties of the revised age model. The timing of the abrupt Holocene surface hydrographic events reconstructed from the core, particularly 8.2 ka, expressed pronouncedly in the mud area on the inner shelf of the ECS appear to be coincident with the records from the North Atlantic, the South China Sea and an adjacent land cave and Greenland ice cores, suggesting global climatic teleconnections. The abrupt climate changes during the Holocene displays periodicities of 820–830 years and 350–420 years, which may be related to solar activity but suggests a robust regional feature of hydrographic changes in the western tropical Pacific. We conclude that the singularity of the particular hydrographic patterns and mechanisms responsible for the patterns and periodicities of these abrupt events merits further studies by more intensive dating controls and novel proxy reconstructions.